Relationship between alveolar PO2 and the rate of p-nitroanisole O-demethylation by the cytochrome P-450 pathway in isolated rabbit lungs. - Fisher, A B (1979)
The relationship between alveolar PO2 and the rate of O-demethylation of p-nitroanisole, a model substrate for cytochrome P-450 -linked mixed-function oxidation, was evaluated in the isolated rabbit lung perfused with Krebs-Ringer bicarbonate buffer. The appearance of the product, p-nitrophenol, in the pulmonary perfusate was measured spectrophotometrically, The PO2 of the ventilating gas was varied with an accurate gas mixing pump and measured with an electrochemical O2 analyzer. In control lungs ventilated with 5% CO2 in air, the rate of p-nitrophenol production was approximately equal to 3.1 +/- 0.04 (mean +/- SE; n = 9) mumol/h per g dry wt. p-Nitrophenol production was unaltered when O2 in the ventilating gas was decreased to 1%, but it was depressed reversibly when alveolar O2 WAS 0.1% OR LESS AND WAS ABOLISHED DURING VENTILATION WITH 0.005% O2. The rate of the reaction was inhibited by 50% when alveolar PO2 was 0.3 mm Hg representing and intracellular [O2] OF approximately equal to muM. In the presence of metyrapone (0.1--1 mM), an inhibitor of cytochrome P-450-dependent reactions, p-nitrophenol production was 0.07--0.17 mumol/h per g dry wt. Ventilation of lungs with varying CO concentration in 20% O2 resulted in 50% inhibition of p-nitrophenol production when CO concentration was 10% (CO/O2 = 0.5). These results indicated that O-demethylation of p-nitroanisole by the lung is a cytochrome P-450-dependent reaction and that its rate is not affected until alveolar PO2 is less than 1 mm Hg.